Seven Days of Nectar: Contemporary Oral Performances of the Bhagavatapurana, by McComas Taylor - Knuppel, Anandi Silva (Religions of South Asia, 2018)
Seven Days of Nectar: Contemporary Oral Performances of the Bhagavatapurana, by McComas Taylor. New York: Oxford University Press, 2016. 248 pp., 105.00. ISBN 978-0-190-61191-0.